SOLVENT EXTRACTION OPTIMIZATION OF CHLOROPHYLL DYE FROM CONOCARPUS LANCIFOLIUS LEAVES - Jassim, Nawras Jameel (Journal of Engineering and Technological Sciences, 2020)
Recently, the green food industry has started using chlorophyll dye as a healthy and safe color additive for food and beverages. In this study, a conventional extraction technique was used to extract chlorophyll dye from Conocarpus lancifolius leaves, using 80% acetone as solvent. Taguchi?s L25 orthogonal array was utilized to optimize the extraction parameters with total chlorophyll dye yield as the response. The optimum extraction conditions were 75 minutes of extraction time, 33.5 °C extraction temperature and a 118 ml/g solvent to raw leaves ratio. Analysis of variance using Minitab18 was conducted to identify the most significant extraction parameters and available interactions. It was found that the chlorophyll dye yield from Conocarpus lancifolius leaves is mostly dependent on extraction time, followed by mixing ratio and temperature. The analysis showed a large interaction between the extraction parameters studied. The experimental chlorophyll dye yield was in close agreement with the predicted model. The adequacy of the predicted model was confirmed by an experiment conducted under the optimal conditions, given a 3.9% error percentage.